OPERATING RANGES OF DYNAMIC SYSTEMS WITH NONLINEAR QUALITY REGULATORS - Glazok , O. M. (Problems of Informatization and Management, 2005)
The method of analytical design of regulators for nonlinear dynamic controlled systems with the use of modified quality functional is investigated. The influence of the values of the attenuation parameters with which the regulator is synthesized on the behavior of the controlled system is considered. The boundaries of the set of states from which the system will return to the equilibrium point are determined.